Energy storage electrode composite material and preparation method thereof

By preparing the hollow tubular structure of Fe2O3 and coated with graphene, the agglomeration problem during Fe2O3 and graphene is solved, the electrochemical energy storage performance and cycling stability are improved, and high energy density and good magnification characteristics are achieved.

CN117894598BActive Publication Date: 2025-01-03CHONGQING UNIV OF ARTS & SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410096772.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2025-01-03
Estimated Expiration
2044-01-24

AI Technical Summary

Technical Problem

When Fe2O3 is a negative electrode material for supercapacitors, it has poor rate retention and low energy density due to its inherent low conductivity, and is prone to agglomeration when recombined with graphene, affecting electrochemical properties.

Method used

By preparing α-crystalline Fe2O3 with a hollow tubular structure and covering its surface with graphene, the mass proportion of graphene is controlled between 4.8% and 31.3%. The Fe2O3 nanoparticles are suppressed by using MoO3 nanofiber template and hydrothermal + annealing method. Agglomerate to form a uniform pore structure to improve conductivity.

Benefits of technology

The conductivity and electrochemical energy storage performance of the electrodes have been significantly improved, and the ratio characteristics, cycle stability and durability of the material are improved. The specific capacitance retention rate of Fe2O3 hollow tube/graphene composite material is as high as 87.7% under high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117894598B_ABST
    Figure CN117894598B_ABST
Patent Text Reader

Abstract

A composite material for energy storage electrode, characterized in that: the composite material is composed of α-crystalline Fe2O3 and graphene, wherein Fe2O3 is in a hollow tubular structure, formed by the accumulation of Fe2O3 nanoparticles, and graphene is coated on the surface of Fe2O3, and the mass proportion of graphene is between 4.8% and 31.3%. The Fe2O3 hollow tube / graphene energy storage electrode composite material prepared by the present invention effectively avoids serious aggregation of itself, significantly improves the conductivity of the electrode, and Fe2O3 and graphene have a reasonable content ratio, which effectively improves the electrochemical energy storage performance of the material. The electrode prepared by the Fe2O3 hollow tube / graphene composite material has a specific capacitance of 426.3F / g at a current density of 1A / g. When the current density is increased to 20A / g, its specific capacitance is still as high as 219.1F / g, with excellent rate characteristics, and the specific capacitance retention rate after repeated charge and discharge for 10,000 times is still 87.7%, reflecting the excellent cycle stability and durability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of carbon-based composite electrochemical materials, and in particular to an energy storage electrode composite material and a preparation method thereof. Background Art

[0002] Metal oxides as electrode materials have the advantages of high power density and energy density, large capacity, and good current discharge performance. However, metal oxides as electrode materials also have disadvantages such as large internal resistance, large grains, and low utilization rate during electrode reactions. Initially, RuO 2 As the electrode material of supercapacitor, precious metal oxides such as NiO and MnO have obtained higher specific capacity and better performance than carbon electrodes. 2 SnO 2 、MoO 3 , Fe 2 O 3 wait.

[0003] Fe 2 O 3 It is a transition metal oxide with abundant reserves, low cost and environmental friendliness. It has a high theoretical capacitance value and negative potential working range, and is expected to be developed into a high-performance supercapacitor negative electrode material, and has therefore attracted widespread attention from scientific researchers. However, the current problem facing this material is its inherent low conductivity, which leads to poor rate retention and low energy density. To solve the above problems, the existing technology combines this material with carbon materials to solve this technical problem. However, Fe 2 O 3 When composited with carbon materials such as graphene, graphene tends to agglomerate, and the graphene and Fe 2 O 3 The content ratio cannot be controlled, so the electrochemical energy storage of the composite material does not meet expectations.

[0004] In addition, Fe 2 O 3 It is easy to expand and agglomerate during the charge and discharge process, which seriously affects its electrochemical performance and causes powderization during repeated charge and discharge. 2 O 3 During the charge and discharge process, volume changes such as expansion are likely to occur, leading to increased stress and material pulverization, which reduces its electrochemical performance. The material can be made into nanoscale, but nanoscale materials will cause the material to agglomerate more and also reduce its electrochemical performance. Summary of the invention

[0005] In order to solve the above technical problems, the present invention aims to provide an energy storage electrode composite material having excellent electrochemical energy storage properties.

[0006] Another object of the present invention is to provide a method for preparing the above energy storage electrode composite material. 2 O 3 The problem of graphene agglomeration is solved, and the rate characteristics, cycle stability and durability of the material are effectively improved.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A composite material for energy storage electrode, characterized in that: the composite material is α-crystalline Fe 2 O 3 and graphene, where Fe 2 O 3 It has a hollow tubular structure and is Fe 2 O 3 Nanoparticles are stacked, and graphene is coated on Fe 2 O 3 On the surface, the mass proportion of graphene is between 4.8% and 31.3%.

[0009] Further preferably, the mass proportion of graphene in the composite material is 10.4% to 26.9%.

[0010] It was found during the preparation process that in the prepared composite material, Fe 2 O 3 The content ratio of graphene and Fe has a crucial influence on the electrochemical energy storage performance of the composite material. On the one hand, if the proportion of graphene is small, the conductivity of the composite material is still insufficient, and the electrochemical energy storage is difficult to achieve the expected performance. On the other hand, if the proportion of graphene is large, although it will significantly improve the conductivity of the composite material, due to Fe 2 O 3 If the content of graphene is too low, the overall electrochemical energy storage performance will not be very good. When the mass proportion of graphene is 4.8%~31.3%, the composite material has excellent electrochemical energy storage performance.

[0011] A method for preparing an energy storage electrode composite material, characterized in that it comprises the following steps:

[0012] (1) (NH 4 ) 2 MoO 4 ∙4H 2 MoO was prepared by mixing O aqueous solution with concentrated nitric acid through hydrothermal reaction 3 Nanofibers;

[0013] (2)MoO3 Nanofibers are dispersed in water to form a dispersion, and then mixed with Na 2 SO 4 and FeCl 3 ∙6H 2 O aqueous solution, and then reacted in a water bath. After the reaction, annealing was performed to obtain MoO 3 / Fe 2 O 3 Composite nanofibers;

[0014] (3)MoO 3 / Fe 2 O 3 The composite nanofibers are dispersed in water to form a nanofiber dispersion, and then graphene oxide aqueous dispersion and hydrazine hydrate are added, followed by a water bath reaction.

[0015] Furthermore, in step (1), (NH 4 ) 2 MoO 4 ∙4H 2 In aqueous solution of O, (NH 4 ) 2 MoO 4 ∙4H 2 The dosage ratio of O to water is 1g:160~170mL.

[0016] Further, in step (1), (NH 4 ) 2 MoO 4 ∙4H 2 The volume ratio of the O aqueous solution to the concentrated nitric acid is 5:1, and the volume concentration of the concentrated nitric acid is 65%.

[0017] Furthermore, the temperature of the hydrothermal reaction in step (1) is 170-190° C., and the reaction time is 6-10 hours.

[0018] Furthermore, in the dispersion of step (2), MoO 3 The ratio of nanofiber to water is 1~1.2mg:1mL, Na 2 SO 4 and FeCl 3 ∙6H 2 NaO in aqueous solution 2 SO 4 、FeCl 3 ∙6H 2 The dosage ratio of O and water is 54~58mg:106~110mg:10mL.

[0019] Furthermore, in step (2), the dispersion and the Na-containing 2 SO4 and FeCl 3 ∙6H 2 The volume ratio of the aqueous solution of O is 5:1.

[0020] Furthermore, in step (2), the temperature of the water bath reaction is 85-100° C., and the reaction time is 2-2.5 h.

[0021] Furthermore, the annealing temperature in step (2) is 440-460° C., and the annealing time is 1.5-2.5 h.

[0022] Furthermore, the nanofiber dispersion in step (3) contains MoO 3 / Fe 2 O 3 The dosage ratio of the composite nanofibers to water is 1.5-1.7 mg:1 mL, the concentration of the graphene oxide aqueous dispersion is 1.8-2.2 mg / mL, and the mass fraction of hydrazine hydrate is 40%.

[0023] Furthermore, in step (3), the volume ratio of the nanofiber dispersion, the graphene oxide aqueous dispersion and the hydrazine hydrate is 100:5-80:3-5.

[0024] Furthermore, the temperature of the water bath reaction in step (3) is 80-90 o C, reaction time 1h.

[0025] In the preparation of nano-scale Fe 2 O 3 It was found that Fe 2 O 3 There will be obvious aggregation and Fe 2 O 3 When compounded with graphene, graphene will also have agglomeration problems, resulting in serious overall agglomeration of the final prepared composite material, and Fe 2 O 3 The ratio of MoO to graphene is difficult to control, resulting in poor electrochemical performance. 3 The nanofiber template was made and Fe was in situ generated on its surface by hydrothermal and annealing. 2 O 3 Nanoparticles, eventually forming Fe 2 O 3 to MoO 3 The uniform coating of nanofibers effectively inhibits the Fe 2 O 3 The agglomeration of nanoparticles forms a uniform and developed pore distribution, providing a uniformly dispersed site for the subsequent graphene composite. In the process of graphene composite, the addition of hydrazine hydrate makes the whole system alkaline, effectively dissolving and removing MoO 3template, making Fe 2 O 3 While forming a hollow tube, the graphene oxide is reduced to generate a certain proportion of graphene and evenly adhere to the Fe 2 O 3 surface, making graphene and Fe 2 O 3 The proportion has been effectively controlled.

[0026] The present invention has the following technical effects:

[0027] The Fe prepared by the present invention 2 O 3 In the hollow tube / graphene energy storage electrode composite material, Fe 2 O 3 The composition presents a unique hollow tubular structure with developed pores, which facilitates the penetration, transmission and diffusion of electrolyte ions during the charging and discharging process. Graphene surrounds, covers and adheres to Fe 2 O 3 The hollow tube achieves composite, avoiding serious aggregation, significantly improving the electrode conductivity, and Fe 2 O 3 The reasonable content ratio of Fe and graphene accelerates the transfer and transmission of electrons during the charging and discharging process, effectively improving the electrochemical energy storage performance of the material. These multiple favorable factors synergistically enhance the charge storage capacity of the composite material, giving the material excellent electrochemical energy storage properties. 2 O 3 The specific capacitance of the hollow tube / graphene composite material is 426.3F / g at a current density of 1A / g. When the current density is increased to 20A / g, its specific capacitance is still as high as 219.1F / g, with excellent rate characteristics. After repeated charge and discharge for 10,000 times, the specific capacitance retention rate is still 87.7%, reflecting the excellent cycle stability and durability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : MoO prepared in Example 1 of the present invention 3 Scanning electron microscopy images of nanofibers.

[0029] Figure 2 : MoO prepared in Example 1 of the present invention 3 / Fe 2 O 3 Scanning electron microscope image of the composite nanostructure.

[0030] Figure 3 : Fe prepared in Example 1 of the present invention 2 O 3 Transmission electron microscopy image of hollow tube / graphene composite material.

[0031] Figure 4 : Fe prepared in Example 1 of the present invention 2 O 3 XRD patterns of hollow tube / graphene composites.

[0032] Figure 5 : Fe prepared in Example 1 of the present invention 2 O 3 Nitrogen adsorption–desorption curves of hollow tube / graphene composites.

[0033] Figure 6 : Fe prepared in Example 1 of the present invention 2 O 3 Pore ​​size distribution of hollow tube / graphene composites.

[0034] Figure 7 : Fe prepared in Example 1 of the present invention 2 O 3 Cyclic voltammetry curves of hollow tube / graphene composite as electrode at different scan rates.

[0035] Figure 8 : Fe prepared in Example 1 of the present invention 2 O 3 Charge and discharge curves of hollow tube / graphene composite as electrode at different current densities.

[0036] Fig. 9 : Fe prepared in Example 1 of the present invention 2 O 3 A graph showing the capacitance retention of the hollow tube / graphene composite as an electrode during 10,000 cycles of charge and discharge.

[0037] Fig.10 : Fe prepared in Example 1 of the present invention 2 O 3 The last 10 charge and discharge curves of the hollow tube / graphene composite material as an electrode during 10,000 cycles of repeated charge and discharge. DETAILED DESCRIPTION

[0038] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0039] Example 1

[0040] A method for preparing an energy storage electrode composite material comprises the following steps:

[0041] (1) Add 250 mL of (NH 4 ) 2 MoO 4 ∙4H 2 The O aqueous solution was mixed evenly with 50 mL of concentrated nitric acid with a mass percentage concentration of 65%, and then added into a reactor with a capacity of 500 mL. The reactor was then sealed and placed in an oven for hydrothermal reaction. The hydrothermal reaction was carried out at 180 o C for 8 h and the resulting product MoO 3 The nanofibers are collected and used after centrifugal separation, repeated water washing and sufficient drying;

[0042] (2) 240 mg of MoO 3 The nanofibers were ultrasonically dispersed in a beaker containing 200 mL of water and then 40 mL of 224 mg of Na 2 SO 4 and 432 mg of FeCl 3 ∙6H 2 O aqueous solution was poured into it, and the mixed system was heated at 90 o C water bath for 2 h, the obtained product was separated by centrifugation, repeatedly washed with water and fully dried, and then placed in a muffle furnace at 450 o C for 2 h to obtain MoO 3 / Fe 2 O 3 Composite nanofibers;

[0043] (3) Take MoO 3 / Fe 2 O 3 160 mg of composite nanofibers were placed in a 500 mL beaker, and then 100 mL of water was added for ultrasonic dispersion. Then 30 mL of 2 mg / mL graphene oxide aqueous dispersion and 4 mL of 40% hydrazine hydrate were added to the MoO 3 / Fe 2 O 3 Composite nanofiber aqueous dispersion, and in 85 o C water bath for 1h. After the reaction, the obtained product was centrifuged, repeatedly washed with water and freeze-dried to obtain Fe 2 O 3 Hollow tube / graphene energy storage electrode composite materials.

[0044] The Fe prepared in this example 2 O 3 The graphene content in the hollow tube / graphene energy storage electrode composite material is 23.2%.

[0045] MoO synthesized by hydrothermal method 3The nanofiber template is white and has a relatively smooth surface, which can be seen from its scanning electron microscope image. Figure 1 As shown. 3 Nanofibers as templates, FeCl 3 ∙6H 2 O is the iron source, and through the corresponding liquid phase reaction and annealing treatment, the α-crystalline Fe 2 O 3 Uniformly deposited on the substrate surface to prepare brown MoO 3 / Fe 2 O 3 Composite nanofibers. Its morphology and structure are as follows Figure 2 As shown in the figure, it can be seen that the composite nanofiber has a unique core-shell structure with a rough surface and a core of MoO 3 Nanofibers, the outer surface of which is composed of a large amount of Fe 2 O 3 Nanoparticles are closely packed together. 3 / Fe 2 O 3 Composite nanofibers and graphene are combined and MoO is removed by dissolution 3 template to synthesize Fe 2 O 3 The color of the hollow tube / graphene energy storage electrode composite material also changes to black. Figure 3 It is Fe 2 O 3 Transmission electron microscopy image of hollow tube / graphene composite material shows that Fe 2 O 3 It shows a hollow tubular structure, indicating that MoO 3 The template has been effectively removed, and the curled graphene is wrapped around, coated and adhered to the Fe 2 O 3 The hollow tubes form a highly complex structure and avoid the problem of severe aggregation.

[0046] In order to confirm that Fe 2 O 3 We conducted XRD analysis on the two chemical components in the hollow tube / graphene energy storage electrode composite material, such as Figure 4As shown. The XRD spectrum shows 9 diffraction peaks, among which the broad peak with a 2θ angle of ~25° is attributed to the diffraction signal of the graphene (002) crystal plane, and the peaks with 2θ angles of 23.8°, 33.1°, 35.6°, 40.8°, 49.5°, 54°, 62.4° and 64.1° correspond to the diffraction signals of the (012), (104), (110), (113), (024), (116), (214) and (300) crystal planes of α-crystalline Fe2O3, respectively. In addition to the above diffraction peaks, the XRD spectrum does not show other impurity peaks, further indicating that the MoO3 template has been completely removed.

[0047] Figure 5 It is Fe 2 O 3 Hollow tube / graphene energy storage electrode composites N 2 From the adsorption-desorption curve, it is not difficult to see that there is a hysteresis loop in the relative pressure range of 0.45-1.0, indicating that the composite material has mesoporous characteristics. Figure 6 The pore size distribution diagram further reflects the Fe2O 3 Mesoporous characteristics and pore size distribution of hollow tube / graphene energy storage electrode composites. 2 O 3 The well-developed pores of the hollow tube / graphene energy storage electrode composite material give it a high conductivity of up to 169m 2 / g specific surface area and 0.25 m 3 / g pore volume. The intact hollow tubular structure, abundant pores, high specific surface area and pore volume, and excellent electrical conductivity of the composite material can not only greatly increase the active sites of electrochemical reactions, but also facilitate the penetration, transmission and diffusion of electrolyte ions during the charge and discharge process, and accelerate the transfer and transmission speed of electrons during the charge and discharge process, thereby achieving excellent electrochemical energy storage effects.

[0048] Comparative Example 1

[0049] The difference from Example 1 is that in step (3) of composite graphene, ammonia water is used instead of hydrazine hydrate, and the remaining steps are the same as those in Example 1. 3 It was not effectively removed, and there was obvious residue. 2 O 3 No complete hollow tube is formed. In order to form a hollow tube structure, the water bath temperature in step (3) needs to be adjusted to 100°C and the water bath time is 10 hours. 2 O 3 / The mass proportion of graphene in the graphene composite material is 34.8%, and the graphene shows stacking and agglomeration phenomenon.

[0050] Fe prepared in Comparative Example 1 2 O 3 In the process of graphene / graphene composites, the water bath temperature needs to be increased and the water bath time needs to be extended so that ammonia can effectively remove MoO 3 template, making Fe 2 O 3 The hollow tube is formed. In this process, the synchronous reduction and recombination sites of graphene by ammonia water cannot be effectively regulated, resulting in the formation of graphene and Fe 2 O 3 The composite ratio is unbalanced and some graphene is agglomerated.

[0051] Example 2

[0052] A method for preparing an energy storage electrode composite material comprises the following steps:

[0053] (1) Add 240 mL of (NH 4 ) 2 MoO 4 ∙4H 2 The aqueous solution of O and 48 mL of concentrated nitric acid with a mass percentage concentration of 65% were mixed evenly and added into a reactor with a capacity of 500 mL. The reactor was then sealed and placed in an oven for hydrothermal reaction. The hydrothermal reaction was carried out at 170 o C for 10 h and the resulting product MoO 3 The nanofibers are collected and used after centrifugal separation, repeated water washing and sufficient drying;

[0054] (2) 220 mg of MoO 3 The nanofibers were ultrasonically dispersed in a beaker containing 200 mL of water and then 40 mL of 232 mg of Na 2 SO 4 and 440 mg of FeCl 3 ∙6H 2 O aqueous solution was poured into it, and the mixed system was heated to 100 o C water bath for 2 h, the obtained product was separated by centrifugation, repeatedly washed with water and fully dried, and then placed in a muffle furnace at 460 o C for 1.5 h to obtain MoO 3 / Fe 2 O 3 Composite nanofibers;

[0055] (3) Take MoO 3 / Fe 2 O 3150 mg of composite nanofibers were placed in a 500 mL beaker, and then 100 mL of water was added for ultrasonic dispersion. Then 80 mL of 1.8 mg / mL graphene oxide aqueous dispersion and 5 mL of 40% hydrazine hydrate were added to the MoO 3 / Fe 2 O 3 Composite nanofiber aqueous dispersion, and at 80 o C water bath for 1h. After the reaction, the obtained product was centrifuged, repeatedly washed with water and freeze-dried to obtain Fe 2 O 3 Hollow tube / graphene energy storage electrode composite materials.

[0056] The Fe prepared in this example 2 O 3 The mass proportion of graphene in the hollow tube / graphene energy storage electrode composite material is 31.3%.

[0057] Example 3

[0058] A method for preparing an energy storage electrode composite material comprises the following steps:

[0059] (1) Add 255 mL of (NH 4 ) 2 MoO 4 ∙4H 2 The O aqueous solution was mixed evenly with 51 mL of 65% concentrated nitric acid and added into a 500 mL reactor. The reactor was sealed and placed in an oven for hydrothermal reaction at 190 o C for 6 hours and the resulting product MoO 3 The nanofibers are collected and used after centrifugal separation, repeated water washing and sufficient drying;

[0060] (2) 200 mg of MoO 3 The nanofibers were ultrasonically dispersed in a beaker containing 200 mL of water and then 40 mL of 216 mg of Na 2 SO 4 and 424 mg of FeCl 3 ∙6H 2 O aqueous solution was poured into it, and the mixed system was heated at 85 o C water bath for 2.5 h, the obtained product was separated by centrifugation, repeatedly washed with water and fully dried, and then placed in a muffle furnace at 440 o C for 2.5 h to obtain MoO 3 / Fe 2 O 3 Composite nanofibers;

[0061] (3) Take MoO 3 / Fe 2 O 3 170 mg of composite nanofibers were placed in a 500 mL beaker, and then 100 mL of water was added for ultrasonic dispersion. Then, 5 mL of 2.2 mg / mL graphene oxide aqueous dispersion and 3 mL of 40% hydrazine hydrate were added to the MoO 3 / Fe 2 O 3 Composite nanofiber aqueous dispersion, and at 90 o C water bath for 1h. After the reaction, the obtained product was centrifuged, repeatedly washed with water and freeze-dried to obtain Fe 2 O 3 Hollow tube / graphene energy storage electrode composite materials.

[0062] The Fe prepared in this example 2 O 3 The mass proportion of graphene in the hollow tube / graphene energy storage electrode composite material is 4.8%.

[0063] Example 4

[0064] The energy storage electrode composite material prepared in Example 1 was used as an active material to prepare a supercapacitor electrode and test its electrochemical energy storage properties. The specific steps are as follows:

[0065] The energy storage electrode composite material, acetylene black and polyvinylidene fluoride prepared in Example 1 were placed in an agate mortar in a mass ratio of 8:1:1 and evenly mixed. An appropriate amount of methyl pyrrolidone was dropped into the mortar and then gently ground into a paste. The paste was evenly applied to one side of a rectangular nickel foam with a slender paintbrush. The nickel foam coated with the electrode material was then placed in a tablet press and pressed into a thin sheet, which was then vacuum dried to obtain a thin sheet electrode for testing under a three-electrode system.

[0066] A three-electrode device was built using the thin sheet electrode prepared from the energy storage electrode composite material as the working electrode, Hg / HgO as the reference electrode, a platinum sheet as the counter electrode, and a 3M KOH aqueous solution as the electrolyte to test the electrochemical energy storage properties.

[0067] Figure 7 Fe 2 O 3 The cyclic voltammetry curves of the electrodes prepared from the hollow tube / graphene composite material, the test potential window is -1V~0V, and the scan rate range is 5mV / s~200mV / s. It is obvious that each cyclic voltammetry curve has a wide Faraday hump, showing the characteristics of the pseudocapacitive energy storage mechanism. Figure 8This is the constant current charge and discharge curve of the electrode prepared from the Fe2O3 hollow tube / graphene composite material. The test potential window is also -1V~0V, and the current density range is 1~20A / g. Through theoretical calculations, the maximum specific capacitance of the electrode is as high as 426.3F / g at a current density of 1A / g. When the current density is increased to 20A / g, its specific capacitance still retains 219.1F / g. Compared with the maximum specific capacitance, the degree of reduction in specific capacitance is less than half when the current density is increased by 20 times, indicating that the electrode has excellent rate properties. In addition, this electrode was continuously charged and discharged 10,000 times at a high current density (10A / g). The results are as follows Fig. 9 As shown in the figure, the capacitance decays slowly during the whole process, and the final capacitance retention rate is still 87.7%. The Kunlun efficiency is almost always close to 100%. By observing the last 10 charge and discharge curves, the results are as follows Fig.10 As shown in the figure, the curve shape is intact, showing excellent cycle stability and durability. 2 O 3 These performance indicators of electrodes prepared from hollow tube / graphene composites far exceed the electrochemical performance of many iron oxides, sulfides, phosphides and commercial porous carbon materials.

Claims

1. A method for preparing an energy storage electrode composite material, characterized in that: The steps include: (1) MoO3 nanofibers were prepared by mixing (NH4)2MoO4·4H2O aqueous solution with concentrated nitric acid and then subjecting to hydrothermal reaction; (2) dispersing MoO3 nanofibers in water to form a dispersion, and then mixing with an aqueous solution containing Na2SO4 and FeCl3·6H2O to react in a water bath, and after the reaction, annealing is performed to obtain MoO3 / Fe2O3 composite nanofibers; (3) dispersing MoO3 / Fe2O3 composite nanofibers in water to form a nanofiber dispersion, then adding graphene oxide aqueous dispersion and hydrazine hydrate, and then conducting a water bath reaction, wherein the amount ratio of MoO3 / Fe2O3 composite nanofibers to water in the nanofiber dispersion is 1.5-1.7 mg:1 mL, the concentration of the graphene oxide aqueous dispersion is 1.8-2.2 mg / mL, the mass fraction of hydrazine hydrate is 40%, and the volume ratio of the nanofiber dispersion, the graphene oxide aqueous dispersion and the hydrazine hydrate is 100:5-80:3-5; The composite material is composed of α-crystalline Fe2O3 and graphene, wherein the Fe2O3 has a hollow tubular structure and is formed by the accumulation of Fe2O3 nanoparticles, and the graphene is coated on the surface of the Fe2O3, and the mass proportion of the graphene is between 14.8% and 31.3%.

2. The method for preparing a composite material for energy storage electrode according to claim 1, characterized in that: In the (NH4)2MoO4·4H2O aqueous solution of step (1), the dosage ratio of (NH4)2MoO4·4H2O to water is 1 g: 160-170 mL.

3. A method for preparing an energy storage electrode composite material according to claim 1 or 2, characterized in that: In the step (1), the volume ratio of the (NH4)2MoO4·4H2O aqueous solution to the concentrated nitric acid is 5:

1.

4. The method for preparing a composite material for energy storage electrode according to claim 3, characterized in that: The temperature of the hydrothermal reaction in step (1) is 170-190° C., and the reaction time is 6-10 hours.

5. The method for preparing a composite material for energy storage electrode according to claim 4, characterized in that: In the dispersion of step (2), the ratio of MoO3 nanofibers to water is 1-1.2 mg:1 mL, and the ratio of Na2SO4, FeCl3·6H2O and water in the aqueous solution of Na2SO4 and FeCl3·6H2O is 54-58 mg:106-110 mg:10 mL.

6. A method for preparing a composite material for energy storage electrode according to claim 4 or 5, characterized in that: In the step (2), the volume ratio of the dispersion to the aqueous solution containing Na2SO4 and FeCl3·6H2O is 5:

1.

7. The method for preparing a composite material for energy storage electrode according to claim 6, characterized in that: In the step (2), the temperature of the water bath reaction is 85-100° C., the reaction time is 2-2.5 h, the temperature of the annealing treatment is 440-460° C., and the annealing time is 1.5-2.5 h.